Behavior of platinum stimulating electrodes in physiological media - Rozman, Janez (Kovine zlitine tehnologije, 1998)
Electrical stimulation of neuro-muscular system generates a response in excitable cells by an electrical field between two electrodes produced by the flow of ions, i.e. ionic current, in the biological fluid. The compatibility of a chronic neural prostheses requires that the electrical charge must be delivered without producing toxic reactions products or degrading the electrode. For a given electrode there is a limit to the quantity of charge that can be injected in either the anodic or cathodic direction with reversibile surface processes. This limit will depend upon the size of the electrode, its geometry, and the parameters of the stimulating waveform. To determine this limit experimentally, knowledge of the potential range over which they can occur is required. The electrochemical technique of cyclic voltammetry can delineate an operational potential window between hydrogen and oxygen evolution. Keeping the electrode potential within this window during pulsing guarantees that water electrolysis reaction will not occur. The study reported here seeks to characterize platinum electrode behavior of the multielectrode spiral cuff system for selective stimulaation of different superficial regions of peripheral nerves in a protein containing solution. Each platinum electrode of the cuff system had a flat geometric surface of 2 ?$mm^2$?. In a typical cyclic voltammetry experiment, the potential of the tested electrode versus a Saturated Calomel Electrode (SCE) was cycled at an appropriate rate between two potential limits. All measurements have been carried out using a specially designed electrochemical cell at 37°C, and the Potentiostat/Galvanostat (Princeton Applied Research). Besides, investigations of surfaces of electrodes using resolution AES method were performed.
Keywords: živčevje; električna stimulacija; platina; elektrode